(3EOGQI GdeSJTajGJ hGdeQGcR GdUMjI (B/s - (3LdOI, Sdje HWQSs ((3YeGf(B: s (3OGQ GdTQhb(B, s, 2007)
(3GdJWhQ GdJGQjNj ddeSJTajGJ,hXGFa hJUfja GdeSJTajGJ hGdYhGed GdeDKQI aj JWhQgG GdQaGg hGdUMI hGdSdGeI GdYGeI ddYGedjf,JNWjW EfTGA GdeSJTajGJ,GdJfXje GdOGNdj ddeSJTajGJ,eYGjjQ Jbhje GdCOGA aj GdeSJTajGJ,EOGQI GdSLdGJ GdWHjI,GdSLdGJ GdWHjI aj GdCQOf,GSJNOGe GdMGShH aj GdeSJTajGJ,GdJCejf GdWHj aj TQcI Cdjch GdYGdejI,MGdI OQGSjI(B-(3eSJTai (B((3GdafGQJjQ(B)(3aj GdSYhOjI,Mbhb GdeSfjf aj GdYGde,fUGFM WHjI YGeI hGdahGFO GdZPGFjIs
(3HHdjhZQGajG(B:(3U U(B.245-247s
Keywords: (3GdNOeGJ GdUMjIs